2022
DOI: 10.7759/cureus.26099
|View full text |Cite
|
Sign up to set email alerts
|

Short Stature and Celiac Disease in Children (5 to 16 Years) Presenting at a Tertiary Care Hospital in Peshawar

Abstract: Background: Malabsorption is the typical presentation of celiac disease in early childhood, whereas older children can present with extra-intestinal symptoms including short stature and delay in pubertal development.Objective: To determine the frequency of celiac disease in shortening of stature in children.Material and methods: This descriptive, cross-sectional study was conducted at the Pediatric Department in Lady Reading Hospital, Peshawar, on 152 short stature children of both genders aged 5 to 16 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The mean age of the children is 7.7±3.3 years in our study which is comparable with other local and regional studies 9,14,15 . Data stratification according to gender has shown female preponderance in our study: there was significant relationship between asymptomatic CD and female gender (P value= 0.08).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The mean age of the children is 7.7±3.3 years in our study which is comparable with other local and regional studies 9,14,15 . Data stratification according to gender has shown female preponderance in our study: there was significant relationship between asymptomatic CD and female gender (P value= 0.08).…”
Section: Discussionsupporting
confidence: 91%
“…A study conducted in Saudi Arabia showed the incidence of Confirmed CD as 10.9% and Potential CD as 4.3% in children with short stature 8 . A recent study done in Peshawar showed the prevalence of celiac disease to be 33% in children with short stature 9 .…”
Section: Introductionmentioning
confidence: 99%
“…supporting the link between small stature and CD, although their research objectified a prevalence of only 10.9% of the total number of included patients ( 75 ). Currently, it is considered that up to 1/3 of children with short stature may have associated CD, independent of the age and gender of the patients, but this is controversial ( 76 , 77 ). In order to practically exemplify the usefulness of knowing the connection between the two entities, we bring into discussion the case of a 4-year-old girl, who was in the records since the age of 4 months for low growth rate, accompanied by malnutrition, without systemic damage (gastrointestinal, renal or endocrinological).…”
Section: Atypical Forms Of Celiac Diseasementioning
confidence: 99%